2015
DOI: 10.2337/diaspect.28.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Recruitment of Adults With Type 2 Diabetes for a Physical Activity Intervention

Abstract: Recruiting sufficient numbers of participants for physical activity trials for individuals with diabetes can be difficult because there are often many behavioral demands for participants, and inclusion and exclusion criteria can be extensive. This study examined the recruitment strategies used for a randomized, controlled trial designed to investigate the efficacy of an automated telephone intervention to promote physical activity in adults with type 2 diabetes in an urban Veterans Administration health care s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…This result is not unexpected as there is recent evidence that approximately 30 % of adults with type 2 diabetes were found to meet physical activity guidelines [ 1 ]. A finding which is much smaller compared to another recent RCT recruiting type 2 diabetes patients to an automated, interactive voice-response telephone intervention to promote physical activity behaviours in adults with type 2 diabetes, which excluded 26 % of potential participants due to physical activity levels [ 4 ].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…This result is not unexpected as there is recent evidence that approximately 30 % of adults with type 2 diabetes were found to meet physical activity guidelines [ 1 ]. A finding which is much smaller compared to another recent RCT recruiting type 2 diabetes patients to an automated, interactive voice-response telephone intervention to promote physical activity behaviours in adults with type 2 diabetes, which excluded 26 % of potential participants due to physical activity levels [ 4 ].…”
Section: Discussionmentioning
confidence: 94%
“…While it is difficult to compare the success rate of our mass mail-out campaign to other trials given the varying eligibility criteria, our rate is slightly above that reported in the Diabetes Prevention Program (DPP) conducted in the United States, where 29 % of its randomised participants were recruited via direct mass mail-outs into their multi-centre RCT aimed at discovering whether modest weight loss through dietary changes and increased physical activity or treatment with oral diabetes medication could prevent or delay the onset of type 2 diabetes in those at high risk for the condition [ 15 ]. The ability of mass mail-outs to target a large number of participants at a relatively low cost, combined with the reported success of this strategy to yield a high number of eligible participants in both healthy and clinical populations, has in recent years led to this approach becoming an integral part of many recruitment plans [ 4 , 16 18 ]. From our experience, when implementing mass mail-outs as a recruitment strategy it is the choice of the mail-out lists which are likely to contribute to its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations